Brill's Companion to Euripides (2 Vols) - Markantonatos, Andreas (Brill's Companions to Classical Studies, 2020)
Intro -- ‎Contents -- ‎Preface -- ‎Abbreviations -- ‎Figures -- ‎Notes on Contributors -- ‎Introduction (Markantonatos) -- ‎Part 1. The Poet and His Work -- ‎Chapter 1. Life of Euripides (Tyrrell) -- ‎Chapter 2. The Textual Tradition of Euripides' Dramas (Finglass) -- ‎Chapter 3. Alcestis (Iakov) -- ‎Chapter 4. Medea (Kelly) -- ‎Chapter 5. Children of Heracles (Carter) -- ‎Chapter 6. Hippolytus (Mueller) -- ‎Chapter 7. Andromache (Scharffenberger) -- ‎Chapter 8. Hecuba (Tzanetou) -- ‎Chapter 9. Suppliant Women (Morwood) -- ‎Chapter 10. Heracles (Dubischar) -- ‎Chapter 11. Ion (Gibert) -- ‎Chapter 12. Trojan Women (Poe) -- ‎Chapter 13. Electra (Barrett) -- ‎Chapter 14. Iphigenia among the Taurians (Rabinowitz) -- ‎Chapter 15. Helen (Griffiths) -- ‎Chapter 16. Phoenician Women (Swift) -- ‎Chapter 17. Orestes (Ringer) -- ‎Chapter 18. Bacchae (Billings) -- ‎Chapter 19. Iphigenia at Aulis (Gregory) -- ‎Chapter 20. Rhesus (Fantuzzi) -- ‎Chapter 21. Fragments and Lost Tragedies: Alexandros and Later Euripidean Tragedy (Karamanou) -- ‎Chapter 22. Euripides and Satyr Drama (Shaw) -- ‎Part 2. Euripidean Intertextuality: Epic Poetry and Attic Tragedy -- ‎Chapter 23. Euripides: Epic Sources and Models (Davidson) -- ‎Chapter 24. Intertextuality in Euripidean Tragedy (Pucci) -- ‎Part 3. Euripides the Innovator: Language, Rhetoric, Realism, and Emotion -- ‎Chapter 25. The Language of Euripides (Battezzato) -- ‎Chapter 26. Rhetoric in Euripides (O'Sullivan) -- ‎Chapter 27. Realism in Euripides (Lloyd) -- ‎Chapter 28. Emotion in Euripides (Visvardi) -- ‎Contents -- ‎Abbreviations -- ‎Figures -- ‎Part 4. Image, Chorus, and Performance -- ‎Chapter 29. Text and Image: Euripides and Iconography (Hart) -- ‎Chapter 30. Euripides and Art, Artifacts, and the Technical Vocabulary of Craft (Stieber) -- ‎Chapter 31. Euripidean Stagecraft (Miles).